2002
DOI: 10.1002/mrm.10058
|View full text |Cite
|
Sign up to set email alerts
|

Renal T perfusion using an iron oxide nanoparticle contrast agent—influence of T1 relaxation on the first‐pass response

Abstract: Quantitative perfusion measurements require accurate knowledge of the correlation between first-pass signal changes and the corresponding tracer concentration in tissue. In the present study, a detailed analysis of first-pass renal cortical changes in T 1 and T * 2 following bolus injection of the iron oxide nanoparticle NC100150 Injection was investigated in a pig model using a double-echo gradient-echo sequence. The estimated change in 1/T* 2 during first pass calculated from single-echo sequences was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…This unexpected result is in contradiction to previous studies, in which the susceptibility-weighted signal was thought to have been contaminated predominantly by R1 (22). In analogy with the conclusions derived from perfusion experiments conducted with truly confined intravascular contrast agents, this error can potentially be eliminated using a double-echo gradient-echo sequence, which however may critically compromise the temporal resolution (22)(23)(24). For example, a single-shot double-echo EPI has been attractive for cerebral perfusion due to its inherent R2 dependency, but this technique is somewhat hampered by the limited number of slices available (25).…”
Section: Discussionmentioning
confidence: 99%
“…This unexpected result is in contradiction to previous studies, in which the susceptibility-weighted signal was thought to have been contaminated predominantly by R1 (22). In analogy with the conclusions derived from perfusion experiments conducted with truly confined intravascular contrast agents, this error can potentially be eliminated using a double-echo gradient-echo sequence, which however may critically compromise the temporal resolution (22)(23)(24). For example, a single-shot double-echo EPI has been attractive for cerebral perfusion due to its inherent R2 dependency, but this technique is somewhat hampered by the limited number of slices available (25).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results indicate that dysprosium‐based relative cerebral blood volume (rCBV) maps are superior to those obtained with gadolinium chelates (53, 54). USPIO particles designed for bolus injection can be used as susceptibility contrast agents to study tissue perfusion (55, 56). Encouraging early clinical results using USPIO particles are beginning to appear in the literature (57, 58).…”
Section: T2*‐weighted Imaging Following Ecf Agent Administrationmentioning
confidence: 99%
“…Although most UPSIOs are known to remain in the intravascular compartment, the water exchange between blood and interstitum will to some extent reduce the spin-lattice relaxation time (denoted as T1). The results from the study by Bjørnerud et al indicated that T1 effects can lead to a significant underestimation of perfusion even in the absence of extravascular leakage, as reflected in the area and peak height of the first-pass curve following bolus injection of iron oxide nanoparticles [26]. This effect was not taken into consideration in our study.…”
Section: Article In Pressmentioning
confidence: 81%